2005
DOI: 10.1161/01.atv.0000187470.31662.fe
|View full text |Cite
|
Sign up to set email alerts
|

The Lamina Adventitia Is the Major Site of Immune Cell Accumulation in Standard Chow-Fed Apolipoprotein E–Deficient Mice

Abstract: Objective-Cells of adaptive immunity have been implicated in atherogenesis. Though substantial information is available on immune cells in atherosclerotic lesions of the lamina intima, cells in the lamina adventitia have received less attention. Methods and Results-The composition of immune cells in the innominate artery and abdominal aorta was examined in young, adult, and old apolipoprotein (apo) E Ϫ/Ϫ and wild-type mice on standard mouse chow. In the innominate artery of apoE Ϫ/Ϫ mice, adventitial T cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
216
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(226 citation statements)
references
References 44 publications
8
216
0
2
Order By: Relevance
“…In support of this hypothesis, microarray analysis of human carotid atherosclerotic plaque tissue by other groups has indicated that SMPDL3A forms part of a gene expression signature that is indicative of inflamed foam cellrich plaque tissue (38), and SMPDL3A is the fifth most up-regulated mRNA in symptomatic (unstable) plaque tissue obtained from carotid endarterectomy patients (39). Furthermore, our re-analysis of publicly available microarray expression data using the NCBI GEO database and GEO2R tool (40) (accession number GSE21419) reveals that Smpdl3a mRNA is significantly up-regulated in laser-capture microdissected atherosclerotic plaques from apoE Ϫ/Ϫ mice, versus the adjacent healthy adventitial tissue (41,42). In this study, neither Smpd1/aSMase nor Smpdl3b mRNA were up-regulated in plaques versus healthy arterial tissue, providing in vivo support of our observation that transcriptional regulation of SMPDL3A is highly distinct from that of its closest homologs.…”
Section: Discussionmentioning
confidence: 91%
“…In support of this hypothesis, microarray analysis of human carotid atherosclerotic plaque tissue by other groups has indicated that SMPDL3A forms part of a gene expression signature that is indicative of inflamed foam cellrich plaque tissue (38), and SMPDL3A is the fifth most up-regulated mRNA in symptomatic (unstable) plaque tissue obtained from carotid endarterectomy patients (39). Furthermore, our re-analysis of publicly available microarray expression data using the NCBI GEO database and GEO2R tool (40) (accession number GSE21419) reveals that Smpdl3a mRNA is significantly up-regulated in laser-capture microdissected atherosclerotic plaques from apoE Ϫ/Ϫ mice, versus the adjacent healthy adventitial tissue (41,42). In this study, neither Smpd1/aSMase nor Smpdl3b mRNA were up-regulated in plaques versus healthy arterial tissue, providing in vivo support of our observation that transcriptional regulation of SMPDL3A is highly distinct from that of its closest homologs.…”
Section: Discussionmentioning
confidence: 91%
“…In atherosclerosis, lymphocyte infiltration in the adventitia has been known for a long time (35,36), but description of its B cell component is more recent (7)(8)(9)(10)(11)(12)(13). Adoptive transfer experiments showed that vascular wall B lymphocytes constitutively home within arterial regions prone to lesion development (6,7,15,28), indicating a high degree of specialization.…”
Section: Discussionmentioning
confidence: 99%
“…B lymphocytes represent a minor component of tunica intima in normal as well as atherosclerotic vessels (7)(8)(9)(10)(11)(12)(13). However, B lymphocytes and plasma cells accumulate in lamina adventitia adjacent to arterial plaques of human patients and of atherosclerosis-prone mice and their numbers generally parallel the severity of vascular lesions (8)(9)(10)(11)(12)(13)(14)(15). The structural organization of the inflammatory infiltrates ranges from solitary cells and small lymphoid cell clusters in early lesions to densely clustered cellular aggregates in advanced atherosclerosis.…”
mentioning
confidence: 99%
“…The morphology of the inflammatory changes found in human atherosclerotic lesions 56 and ApoE-deficient mice aorta 57 suggested that immune mechanisms might be implicated in atherogenesis. Changes in the immune response in GaL3-null mutant mice infected with Toxoplasma gondii 58 indicated that GaL3 plays a regulatory role in both the adaptive and innate immune response to pathogens.…”
Section: Discussionmentioning
confidence: 99%